Remoção de metais pesados utilizando resina Amberlite IR-120 em sistema batelada - Franco, Pietro Escobar (2011)
This study evaluated the removal of heavy metal íons Zn+2 and Ni+2 through the íon exchange process using a cationic resin Amberlite IR-120/Na+. The characterization of wastewater from an industry of electroplating was performed and the results were the basis for obtaining the aqueous solution used at work. Experiments were performed in batch system for the valuation of ion exchange kinetics of the binary systems Ni+2–Na+, Zn+2–Na+ and the ternary system Ni+2–Zn+2–Na+ in the initial concentrations of 20ppm and 200ppm, in the conditions of pH 4.5, agitation speed of 150rpm and 25ºC. Two models were tested to obtain kinetic parameters of ion exchange. In the simulation of kinetic model in which the ion exchange reaction was considered the limiting step during the model does not fit the experimental data. A second simulation, where the diffusion in the resin (linear driving force model) was assumed to be limiting step had better fit and evidence for the hypothesis that the experimental conditions the ion exchange process presents diffusional limitations. The value of mass transfer coefficients in the resin (ks) varied from 0.0032 to 0.043min-1. Kinetic studies showed that equilibrium is reached around 400 minutes for the systems with initial concentration of 20ppm and 60 minutes for systems with initial concentration of 200ppm. Experiments to obtain data of ion exchange equilibrium were performed for the binary systems Ni+2–Na+, Zn+2–Na+ and for the ternary system Ni+2–Zn+2–Na+ at concentrations of 160ppm and 300ppm (pH 4.5, agitation speed of 150rpm and 25ºC). The isotherms were modeled using the law of mass action ideal and not ideal. The Bromley and Wilson models were used to calculate the activity coefficient in solution and resin. Simulations were conducted for determining the value of the constant and equilibrium thermodynamics of the interaction parameters of Wilson. The results showed that the law of mass action is not ideal fits well the experimental data of binary systems. The simulation of the ternary equilibrium system was accomplished using a predictive, based on the interaction parameters of Wilson and equilibrium constants provided by the modeling of binary systems. The data predicted by the model were compared with experimental data and the results showed that the model was able to predict the behavior of the ternary system. The affinity of the studied ions with Amberlite IR-120 showed the following order: Zn+2 Ni+2 > Na+. For all experiments conducted in this study, the variation of pH and stoichiometry during the experiments were evaluated. For the parameter pH, speciation graphics were done using the HYDRA software and the results show that ions of interest in the solutions (Zn+2 and Ni+2) were above 95%. The average deviation from stoichiometry was less than 8%.